Intersectionnalité: une introduction - Bilge, Sirma; Hill Collins, Patricia (Éditions Amsterdam/Multitudes, 2022)
Lieu commun dans les sciences sociales et dans certains cercles militants, féministes et antiracistes en particulier, la notion d’intersectionnalité alimente dernièrement l’une des grandes paniques morales dont notre époque est coutumière : elle serait synonyme de « communautarisme », de « séparatisme ». Ce n’est absolument pas le cas, comme le montre ce livre riche, synthétique et vivant, qui a pour ambition d’introduire le concept auprès d’un large lectorat. Il s’agit d’un outil d’analyse des situations de tort, généralement constituées d’oppressions imbriquées. L’analyse intersectionnelle ne consiste pas à plaquer des notions génériques (la triade « race, classe, genre ») sur des faits, mais à développer une perception fine et située du caractère relationnel des oppressions. L’intersectionnalité est en outre une pratique critique ayant la justice sociale pour horizon. En ce sens, elle ne se réduit pas au champ académique, loin de là. Les autrices font commencer son histoire dans les années 1960-1970, avec les pratiques intellectuelles et politiques de femmes non blanches et, plus spécifiquement encore, avec le féminisme noir et chicano de cette période. Puis elles expliquent comment cette approche s’est institutionnalisée et mondialisée à partir de la fin des années 1980. La pédagogie critique inspirée de Paulo Freire constitue un autre axe généalogique, plus inattendu, développé dans l’ouvrage. Ni communautariste, ni individualiste, ni victimaire, l’approche intersectionnelle souligne donc le caractère social et concret des identités, individuelles comme collectives, dans une perspective émancipatrice.
Keywords: approches et analyses; com5170; cours; discipline; histoire et politique; intersectionnalité; justice sociale; outils; ouvrages de références; premier cycle; projet charge mentale; sciences humaines; sociologie; thématiques

The Routledge handbook of disability and sexuality - Shuttleworth, Russell; Mona, Linda (Routledge international handbooks, 2021)
This handbook provides a much-needed holistic overview of disability and sexuality research andscholarship. With authors from a wide range of disciplines and representing a diversity of nationalities, it provides a multi-perspectival view that fully captures the diversity of issues and outlooks. Organised into six parts, the contributors explore long-standing issues such as the psychological, interpersonal, social, political and cultural barriers to sexual access that idsabled people face and their struggle for sexual rights and participation. The volume also engages issues that have been on the periphery of the discourse, such as sexual accomodations and support aimed at facilitating disabled people's sexual well-being; the socio-sexual tensions confronting disabled people with intersecting stigmatised identities such as LGBTBI or asexual; and the sexual concerns of disabled people in the Global South. It interrogates disability and sexuality from diverse perspectives, from more traditional psychological and sociological models, to various subversive and post-theoretical perspectives and queer theory. This handbook examines the cutting-edge, and sometimes ethically contentious, concerns that have been repressed in the field. With current, international and comprehensive content, this book is essential reading for students, academics and researchers in the areas of disability, gender and sexuality, as well as applied disciplines such as healthcare pratictionners, counsellors, psychology trainees and social workers.
Keywords: EDI; LGBTQIA2+; accessibilité; approches et analyses; capacitisme; care; corps; cours; discipline; histoire et politique; identités LGBTQIA2+; intersectionnalité; outils; ouvrages de références; premier cycle; ressource en ligne; santé; sciences de la santé; sciences humaines; sex1911; sex1920; sexologie; sexualité; systèmes d'oppressions; thématiques; travail social; études critiques du handicap

Intersectional pedagogy : Complicating identity and social justice - Case, Kim A. (Routledge, 2017)
Intersectional Pedagogy explores best practices for effective teaching and learning about intersections of identity as informed by intersectional theory. Formatted in three easy-to-follow sections, this collection explores the pedagogy of intersectionality to address lived experiences that result from privileged and oppressed identities. After an initial overview of intersectional foundations and theory, the collection offers classroom strategies and approaches for teaching and learning about intersectionality and social justice. With contributions from scholars in education, psychology, sociology and women’s studies, Intersectional Pedagogy include a range of disciplinary perspectives and evidence-based pedagogy.
Keywords: approches et analyses; discipline; formations; féminisme décolonial; identités; intersectionnalité; justice sociale; outils; ouvrages de références; psychologie; pédagogie; ressource en ligne; sciences de l'éducation; sciences humaines; sociologie; thématiques; études de genres

The Routledge companion to feminist philosophy - Garry, Ann; Khader, Serene J.; Stone, Alison (Routledge philosophy companions, 2017)
"The Routledge Companion to Feminist Philosophy is an outstanding guide and reference source to the key topics, subjects, thinkers, and debates in feminist philosophy. Fifty-six chapters, written by an international team of contributors specifically for the Companion, are organized into five sections: (1) Engaging the Past; (2) Mind, Body, and World; (3) Knowledge, Language, and Science; (4) Intersections; (5) Ethics, Politics, and Aesthetics. The volume provides a mutually enriching representation of the several philosophical traditions that contribute to feminist philosophy. It also foregrounds issues of global concern and scope; shows how feminist theory meshes with rich theoretical approaches that start from transgender identities, race and ethnicity, sexuality, disabilities, and other axes of identity and oppression; and highlights the interdisciplinarity of feminist philosophy and the ways that it both critiques and contributes to the whole range of subfields within philosophy."--The publisher.
Keywords: afro-féminisme; approches et analyses; autonomie; bioéthique; care; cours; cycles supérieurs; discipline; environnement; esthétique; fem9000; féminisme africain; féminisme autochtone; féminisme décolonial; féminismes noirs; identité; injustices épistémiques; intersectionnalité; justice sociale; matérialité; objectivité; outils; ouvrages de références; philosophie; philosophie féministe; phénoménologie; politique de genre; queer; rationnalité; religion; sciences humaines; subjectivité; thématiques; théorie du contrat social; transféminisme; écologie; éthique; éthique du care; études critiques de la race; études critiques du handicap

The Routledge handbook of epistemic injustice - Kidd, Ian James; Medina, José; Pohlhaus, Gaile M. (Routledge handbooks in philosophy, 2017)
In the era of information and communication, issues of misinformation and miscommunication are more pressing than ever. Epistemic injustice--one of the most important and ground-breaking subjects to have emerged in philosophy in recent years--refers to those forms of unfair treatment that relate to issues of knowledge, understanding, and participation in communicative practices. The Routledge Handbook of Epistemic Injustice is an outstanding reference source to the key topics, problems, and debates in this exciting subject. The first collection of its kind, it comprises over thirty chapters by a team of international contributors, divided into five parts: Core Concepts; Liberatory Epistemologies and Axes of Oppression; Schools of Thought and Subfields within Epistemology; Socio-political, Ethical, and Psychological Dimensions of Knowing; Case Studies of Epistemic Injustice. As well as fundamental topics such as testimonial and hermeneutic injustice and epistemic trust the Handbook includes chapters on important issues such as social and virtue epistemology, objectivity and objectification, implicit bias, and gender and race. Also included are chapters on areas in applied ethics and philosophy, such as law, education, and healthcare. The Routledge Handbook of Epistemic Injustice is essential reading for students and researchers in ethics, epistemology, political philosophy, feminist theory, and philosophy of race. It will also be very useful for those in related fields, such as cultural studies, sociology, education, and law.
Keywords: approches et analyses; capacitisme; cours; cycles supérieurs; discipline; fem9000; hétérosexisme; injustices épistémiques; intersectionnalité; outils; ouvrages de références; philosophie; racisme; santé; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; épistémologie; éthique; études critiques de la race; études critiques du handicap

Arts visuels - Foucher Zarmanian, Charlotte (Encyclopédie critique du genre : corps, sexualité, rapports sociaux, 2016)
"Arts visuel" est l'un des soixante-six textes thématiques de cette encyclopédie explorent les reconfigurations en cours des études de genre. Trois axes transversaux organisent cette enquête collective: le corps, la sexualité, les rapports sociaux. Les inégalités liées au genre sont de plus en plus envisagées en relation avec celles liées à la classe sociale, la couleur de peau, l'apparence physique, la santé ou encore l'âge. Cette approche multidimensionnelle des rapports sociaux a transformé radicalement les manières de penser la domination au sein des recherches sur le genre. En analysant les concepts, les enquêtes empiriques et les débats caractéristiques de ces transformations saillantes, les contributrices et contributeurs de cet ouvrage dessinent une cartographie critique des études de genre en ce début de XXIe siècle.
Keywords: 1900-1999; 2000 à aujourd'hui; approches et analyses; arts visuels et médiatiques; corps; cours; discipline; encyclopédie; europe; fem1000; france; genre; histoire; identité sexuelle; identités LGBTQIA2+; intersectionnalité; occident; outils; premier cycle; recherche en milieux de pratique; ressource en ligne; régions géographiques; sciences humaines; sexualité; thématiques

The SAGE handbook of feminist theory - Evans, Mary (SAGE reference, 2014)
At no point in recorded history has there been an absence of intense, and heated, discussion about the subject of how to conduct relations between women and men. This Handbook provides a comprehensive guide to these omnipresent issues and debates, mapping the present and future of thinking about feminist theory. The chapters gathered here present the state of the art in scholarship in the field, covering: Epistemology and marginality; Literary, visual and cultural representations; Sexuality; Macro and microeconomics of gender; Conflict and peace. The most important consensus in this volume is that a central organizing tenet of feminism is its willingness to examine the ways in which gender and relations between women and men have been (and are) organized. The authors bring a shared commitment to the critical appraisal of gender relations, as well as a recognition that to think ‘theoretically’ is not to detach concerns from lived experience but to extend the possibilities of understanding. With this focus on theory and theorizing about the world in which we live, this Handbook asks us, across all disciplines and situations, to abandon our taken-for-granted assumptions about the world and interrogate both the origin and the implications of our ideas about gender relations and feminism. It is an essential reference work for advanced students and academics not only of feminist theory, but of gender and sexuality across the humanities and social sciences.
Keywords: approches et analyses; corps; cours; discipline; har4600; histoire et politique; intersectionnalité; outils; ouvrages de références; philosophie; phénoménologie; premier cycle; rapports sociaux de sexe; ressource en ligne; sciences de la gestion; sciences humaines; sciences sociales; sex1911; thématiques; violences; économie; épistémologie; études féministes

Le travail social: théories, méthodologies et pratiques - Dorvil, Henri; Harper, Elizabeth; Bibliothèque numérique canadienne (Firme) (Collection Problèmes sociaux & interventions sociales, 2013)
"Ce livre vise à introduire de nouvelles façons de concevoir, de théoriser et d'intervenir sur le social en ce xxie siècle. Il y est non seulement question des fondements du travail social, mais aussi des politiques sociales, des méthodes d'intervention et des enjeux contemporains de la profession. En revisitant d'une manière créative les postulats de base du travail social, les auteurs proposent des lectures inédites des problèmes sociaux, un regard plus nuancé sur les populations marginalisées, un renouvellement des politiques sociales comme levier de citoyenneté ainsi que des pistes d'intervention plus respectueuses des individus, des groupes, des familles et des communautés."-- Site de l'éditeur.
Keywords: approche interculturelle; approches et analyses; cours; discipline; histoire et politique; intersectionnalité; outils; ouvrages de références; premier cycle; sciences humaines; sciences sociales; sex2283; thématiques; travail; travail social